Conselheiros do orçamento participativo nas franjas da sociedade política - de Melo Romão, Wagner [UNESP] (My University, 2011)
This article suggests the need for change in focus of studies on new instances of participation in public policy management, which emerged in the Brazilian re-democratization. Moving away from the literature that addresses the role of civil society in these instances, the author reviews studies on Participatory Budgeting (PB) indicating how such experiences are marked by the dynamics of political society. The argument is reinforced by the presentation of a survey of PB counselors in Osasco-SP, by which we perceive, in general, a role fi lled by political processes of representative democracy. Most councilors compose the fringes of the political society, lie on the rise in, seeking better position in the local political fi eld, internal disputes within the parties and the municipal government. This points the limits of the democratizing potential of the PB, since the expansion of participation in budget decisions would be just within the political society.
Participatory budgeting counselors in the fringes of political society
Keywords: Civil society; Local governmen; Participation; Participatory budgeting; Political society